Islamic banking remedies in Malaysia: bank's remedy for default in bay' bithaman ajil (BBA) financing - Hassan, Rusni; Mokhtar, Norlizah; Othman, Ahmad Azam (2013)
Every person who suffers loss from the act or omission of another may avail himself to remedies to recover from the latter. Remedy is defined in the Oxford Law Dictionary as: “any the methods available at law for the enforcement, protection, or recovery of rights or for obtaining redress for their infringement”. Therefore, when there is infringement, or rather breach of contract, remedies are always available to the innocent parties. This paper attempts to examine the remedies available under Islamic banking in relation to BBA financing especially on the award of damages as one of the remedies under Shari’ah and common law for breach of contract. The damages include ta’widh, gharamah, late payment charges on judgment sum, the balance the selling price etc. This paper will highlight issues on ibra’ that hinder the bank in seeking remedies. The discussion on remedies in BBA financing include the new Shari’ah Resolution issued by Bank Negara Malaysia on 22nd January 2013 with regard to the “formula for the implementation of ibra’ in early settlement cases is also applicable to default cases” and its impact on the Court of Appeal’s decisions in Lim Kok Hoe and Azhar Osman.